1985
DOI: 10.2307/1956116
|View full text |Cite
|
Sign up to set email alerts
|

A New View of Political Accountability for Economic Performance

Abstract: Most political support models imply that in evaluating economic performance, voters use a standard that would provide poor predictions of the future and leave the economy vulnerable to manipulation by vote-hungry politicians. Drawing on macroeconomic theory, we develop a simple standard of evaluation which encompasses a concern not only for current economic outcomes, but also for accurately assessed future consequences of current policies. We find that political support for the president can be explained as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1
2

Year Published

1985
1985
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 20 publications
1
44
1
2
Order By: Relevance
“…The short time frame used here thus assumes that at least in this respect members of Congress are like voters appear to be. (For a contrary view on this matter see Chappell and Keech, 1985 The results of this analysis provide strong support for each of our hypotheses. All coefficients are in the predicted direction.…”
Section: Analysis and Resultssupporting
confidence: 64%
“…The short time frame used here thus assumes that at least in this respect members of Congress are like voters appear to be. (For a contrary view on this matter see Chappell and Keech, 1985 The results of this analysis provide strong support for each of our hypotheses. All coefficients are in the predicted direction.…”
Section: Analysis and Resultssupporting
confidence: 64%
“…Our evidence cannot reject the view that voters are rational, a result that echoes conclusions of Chappell and Keech (1985), Peltzman (1990), and Alesina and Rosenthal (1989). We showed that voting behavior in presidential and congressional elections could reflect marginal voters' awareness of economic constraints and the implications of vote choices for their long-term economic well-being.…”
Section: Resultscontrasting
confidence: 57%
“…Then, we 4Several empirical studies have suggested that voters might be aware of macroeconomic constraints. Chappell and Keech (1985), for one, developed a model of presidential approval based on an explicit voter understanding of macroeconomic constraints as described by an expectations-augmented Phillips curve. This approach was limited by the adoption of an expectational Phillips Curve as the relevant constraint, with an implicit assumption that policymakers' influences on output and unemployment were purely transitory.…”
mentioning
confidence: 99%
“…Beck argues that one ought to think of economic forecasts as conditional expectations where the conditioning variables include competence, administration, and other political variables. He goes on to criticize the strong rational-expectations approach in the popularity-function literature (e.g., Chappell and Keech 1985;Chrystal and Peel 1985) and presents empirical evidence indicating that such a model is suspect. (See also the criticisms of the rational-expectations approach in Hudson 1982, chap.…”
Section: Notesmentioning
confidence: 99%